Is training leaders in functional leadership a useful tool for improving the performance of leadership functions and team effectiveness? - Santos, J. P. (2015)
Departing from the functional leadership model, we propose a team leadership training model as a way to improve the performance of leadership functions and foster team effectiveness. Based on a longitudinal quasi-experimental study involving ninety 6-person teams, 45 trained leaders were compared to 45 untrained leaders at two points in time: before the intervention group was subjected to training experience (time 1), and 6 months after the intervention group had completed their training (time 2). Results showed that, compared to the non-trained leaders, the trained leaders registered an improvement in their enactment of leadership functions. Moreover, these results also showed that training leaders led to an improvement in team effectiveness through the development of team leadership functions. The current findings offer new insights into the way that leaders can improve team effectiveness.